A Systematic, Cross-Model Evaluation of Ensemble Light Scattering Sensors - Abhay Vidwans; Pratim Biswas (Aerosol and Air Quality Research)
Abstract The light scattering particulate matter sensor manufactured by Sharp Inc. (GP2Y1010AU0F) has been evaluated and compared to other commercial off-the-shelf sensors in previous studies and incorporated into commercial air quality monitors to measure aerosol concentration. Despite the popularity of this model, little attention has been given to the later models of the Sharp GP2Y sensor, whose optical chambers are identical but have modified circuitry with features such as enhanced sensitivity and precision. The signal processing front-end of the Sharp GP2Y was further modified by Texas Instruments in a robust analog front-end design with adjustable sensitivity. In this study, we examine six total sensors—the four currently available models of the Sharp GP2Y line dust sensors, and a sensor designed by the Texas Instruments set to two different sensitivity modes. Calibrations were performed in a simple aerosol chamber experiment, and correlations were performed to give rise to characteristic performance parameters of the sensor—sensitivity, precision, accuracy, saturation limit, and limit-of-detection. All six sensors had identical optics and geometry, isolating the effect of signal processing circuit topography on performance parameters for particulate matter measurement. Despite the identical optical chambers and components across the six light scattering sensors, all exhibited distinct performance parameters. Overall, the Sharp sensors performed consistently with the manufacturer claims; the GP2Y1023 exhibited the highest sensitivity (3.16 × 109 m2 W−1 light sensitivity, 0.492 m3 µg−1 mass sensitivity) and the GP2Y1014 exhibited the highest precision (± 10% above 400 µg m−3). The Texas Instruments versions of the sensor exhibited significantly lower sensitivity (< 0.1 m2 W−1 light sensitivity and < 0.03 m3 µg−1) than all Sharp GP2Y sensors, particularly when adjusted to low-gain mode. The low sensitivity of the Texas Instruments sensors makes them well-suited for high concentration environments. This study demonstrates how the performance of light scattering sensors can be readily quantified and how these parameters relate to the point-of-use.